Evidence of riverside ash tree forests in southern Galicia (northwestern Spain) - Amigo, Javier; Pulgar, Iñigo; Izco, Jesús (Lazaroa, 2010)
The paper provides phytosociological data to support the occurrence of ash or ash and elm riverside forests in the southern half of Galicia. As a result of its particular floristic composition (clearly related to the Fraxino Ulmenion minoris suballiance), a new community, to be called Hedero hibernicae-Fraxinetum angustifoliae, is proposed. This forest community, typified at association level, shows a territorial distribution usually associated with temperate sub-Mediterranean or clearly meso-Mediterranean areas of Galicia.